Napoléon III, and Italy. A brief historical survey - Edleston, Robert Holmes. (Harvard local name) (Darlington, Bailey, and Company, Limited, Printers, 1908)
Centres upon Italian nationalism, Garibaldi, and issue of the Papacy.
I. 1830-1860.-II. 1860-65.
Pt. 1 was issued in 1909; pts. II-III have title-pages dated 1911 and 1913, respectively.
Paged continuously.
Bibliography : pt. 1, 4th prelim. leaf; pt. II, p. [514]-[515]
Mode of access: Internet.
Keywords: Napoleon -- III, -- Emperor of the French, -- 1808-1873.; 1848-1870; Italy -- Foreign relations -- France; France -- Foreign relations -- Italy; Italy -- History -- 1848-1870.; History